2016
DOI: 10.1002/nau.23152
|View full text |Cite
|
Sign up to set email alerts
|

Are voiding parameters a marker for the severity of quality of life impairment in women with overactive bladder symptoms?

Abstract: There is no evidence of an association between increasing quality of life impairment and voiding parameters in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…In our study, both women with and without SIBE noted equally high degrees of bother from storage and incontinence symptoms with lower bother from voiding symptoms, but similar bother scores overall. This is in line with previous data that have demonstrated that objective voiding dysfunction may have less of an impact on quality of life than OAB symptoms in women 13 . Similarly, urinary incontinence is associated with a high degree of bother and impact on quality of life 14–16 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, both women with and without SIBE noted equally high degrees of bother from storage and incontinence symptoms with lower bother from voiding symptoms, but similar bother scores overall. This is in line with previous data that have demonstrated that objective voiding dysfunction may have less of an impact on quality of life than OAB symptoms in women 13 . Similarly, urinary incontinence is associated with a high degree of bother and impact on quality of life 14–16 …”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous data that have demonstrated that objective voiding dysfunction may have less of an impact on quality of life than OAB symptoms in women. 13 Similarly, urinary incontinence is associated with a high degree of bother and impact on quality of life. [14][15][16] Our findings raise two questions.…”
Section: Discussionmentioning
confidence: 99%